2020
DOI: 10.1177/0886109920963018
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Based Violence and Alcohol Consumption in Youth Leisure Contexts: Challenges for Spanish Social Work

Abstract: Adolescent leisure contexts in which alcohol are abused have undergone changes in recent decades, with the incorporation of girls/women to more intensive forms of consumption and with new forms of gender-based violence becoming more visible. This article studies the gender differences in the use and enjoyment of time in leisure contexts, the differences in the consumption of alcohol, and the vulnerabilities to which girls/women are subjected to in order to create proposals for Spanish social work intervention.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
1
1
0
1
Order By: Relevance
“…Similar results have been found in previous studies (Dir et al 2017;Kuntsche et al, 2015). In short, these new drinking patterns mean that young women are breaking from the gender norms established in society, particularly from the image of passivity and moderation (Bailey, Griffin & Shankar, 2014;López-Morales;Álvarez-Bernardo & Romo Avilés, 2021;Lyons, Emslie & Hunt, 2014;Patró-Hernández, Nieto & Limiñana-Gras, 2020;Romo-Avilés, García-Carpintero & Pavón-Benítez, 2020;Romo-Avilés et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar results have been found in previous studies (Dir et al 2017;Kuntsche et al, 2015). In short, these new drinking patterns mean that young women are breaking from the gender norms established in society, particularly from the image of passivity and moderation (Bailey, Griffin & Shankar, 2014;López-Morales;Álvarez-Bernardo & Romo Avilés, 2021;Lyons, Emslie & Hunt, 2014;Patró-Hernández, Nieto & Limiñana-Gras, 2020;Romo-Avilés, García-Carpintero & Pavón-Benítez, 2020;Romo-Avilés et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…In this regard, some studies (Gaete & Araya, 2017;Golpe et al, 2017) corroborate that girls already consume more alcohol and tobacco than their male counterparts. However, various studies have shown how in Spain there is greater prejudice directed against young women, in the form of disapproval and reproach of their behaviour; they are judged, and it is considered intolerable that they should get drunk (Lennox et al, 2018;López-Morales, Álvarez-Bernardo & Romo Avilés, 2021;Romo-Avilés, García-Carpintero & Pavón-Benítez, 2020;Romo-Áviles et al, 2018;Ronaldo et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sabemos que los varones siguen consumiendo y causan más lesiones y muertes relacionadas con el alcohol que las mujeres, pero las diferencias se están reduciendo entre adolescentes y adultos jóvenes, principalmente porque el consumo de alcohol entre los hombres ha disminuido más que el consumo de alcohol entre las mujeres y porque las mujeres llevan dos décadas incorporándose a pautas de consumo de las que eran ajenas (Romo-Avilés et al, 2016;White, 2020). Diferentes estudios sugieren que las mujeres presentan mayor riesgo de sufrir problemas de salud relacionados con el abuso de alcohol (Erol & Karpyak, 2015), así como de sufrir violencia sexual (Álvarez-Bernardo et al, 2022;García-Carpintero et al, 2020;López-Morales et al, 2021;Romo-Avilés et al, 2020;Ruiz-Repullo et al 2020;Tarancón et al, 2021).…”
Section: Jóvenes En Las Culturas De La Intoxicaciónunclassified